Medical History of Elderly Patients in the Emergency Setting: Not an Easy Point-of-Care Diagnostic Marker - Tobias Lindner; Anna Slagman; Arthur Senkin; Martin Möckel; Julia Searle (Emergency Medicine International)
Background. Medical histories are a crucially important diagnostic tool. Elderly patients represent a large and increasing group of emergency patients. Due to cognitive deficits, taking a reliable medical history in this patient group can be difficult. We sought to evaluate the medical history-taking in emergency patients above 75 years of age with respect to duration and completeness. Methods. Anonymous data of consecutive patients were recorded. Times for the defined basic medical history-taking were documented, as were the availability of other sources and times to assess these. Results. Data of 104 patients were included in the analysis. In a quarter of patients (25%, n=26) no complete basic medical history could be obtained. In the group of patients where complete data could be gathered, only 16 patients were able to provide all necessary information on their own. Including other sources like relatives or GPs prolonged the time until complete medical history from 7.3 minutes (patient only) to 26.4 (+relatives) and 56.3 (+GP) minutes. Conclusions. Medical histories are important diagnostic tools in the emergency setting and are prolonged in the elderly, especially if additional documentation and third parties need to be involved. New technologies like emergency medical cards might help to improve the availability of important patient data but implementation of these technologies is costly and faces data protection issues.